2020
DOI: 10.1055/s-0040-1708524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Single Intra-Articular Injection of Autologous Adipose Tissue for the Treatment of Osteoarthritis: A Prospective Clinical Study in Dogs

Abstract: Objective The aim of this study was to investigate the safety, feasibility and clinical efficacy of a single intra-articular injection of autologous and purified micro-fragmented adipose tissue for the treatment of osteoarthritis (OA) in dogs. Study Design Twenty-one client-owned dogs with radiographically confirmed OA were recruited into this prospective study. Lameness and discomfort were evaluated by physical examination at day 0 and then 14, 30, 60 and 180 days after injection. Kinetic data and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
3
15
0
Order By: Relevance
“…In this study, seven patients experienced some degree of joint flare, and six out of seven of those patients were in the Allo-MSC group. This is similar to findings reported in other studies involving intra-articular injections, particularly repeat injections of Allo-MSC ( 18 , 38 ). Of the six joint flares in the Allo-MSC group, two were reported to have flare after both injections, two had flare only after the first injection, and another two had flare only after the second injection.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, seven patients experienced some degree of joint flare, and six out of seven of those patients were in the Allo-MSC group. This is similar to findings reported in other studies involving intra-articular injections, particularly repeat injections of Allo-MSC ( 18 , 38 ). Of the six joint flares in the Allo-MSC group, two were reported to have flare after both injections, two had flare only after the first injection, and another two had flare only after the second injection.…”
Section: Discussionsupporting
confidence: 91%
“…MSC are obtained from various sources (e.g., bone marrow, placenta, umbilical cord, etc. ), but adipose-derived MSC have the particular advantage of being both abundant and a more easily harvested resource ( 18 ). Both autologous and allogeneic adipose-derived MSC have been used in veterinary medicine, though to date, there is no consensus on which is safer and more effective ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the long-term outcome showed a substantial decrease in pain severity and interference for the MFAT group supported by a statistical analysis and a statistical significance for pain interference after 180 days ( p < 0.0001). As in the literature on human medicine, an improvement in pain perception is validated in both the short and long term following joint infiltration with MFAT [ 81 , 82 , 83 , 84 ]. Additionally, recent veterinary literature suggests evidence of clinical pain control over 180 days due to intra-articular administration of autologous purified and microfragmented adipose tissue to treat OA in dogs [ 34 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in the literature on human medicine, an improvement in pain perception is validated in both the short and long term following joint infiltration with MFAT [ 81 , 82 , 83 , 84 ]. Additionally, recent veterinary literature suggests evidence of clinical pain control over 180 days due to intra-articular administration of autologous purified and microfragmented adipose tissue to treat OA in dogs [ 34 , 81 ]. One of the authors’ main concerns was the impracticality of making the owner and clinician blind for the treatment group to which the patients belonged [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of MSC-based therapy in veterinary medicine comprises of multiple target diseases, with the vast majority being focused on musculoskeletal conditions such as osteoarthritis (8,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), cruciate ligament disease (9,(35)(36)(37)(38), hip dysplasia (39), bone fractures and lesions (40,41), muscle tears (42,43) and tendinopathies (44,45). Canine clinical studies have also shown promising results for the treatment of diseases of the gastro-intestinal tract (46)(47)(48), central nervous system (49)(50)(51)(52)(53), cardiovascular system (54,55), cutaneous (56)(57)(58)(59) and ocular conditions (60)(61)(62)(63), resulting in encouraging safety and efficacy data (Figure 2).…”
Section: Mesenchymal Stromal Cellsmentioning
confidence: 99%